New superionic halide solid electrolytes enabled by aliovalent substitution in Li3−xY1−xHfxCl6 for all-solid-state lithium metal based batteries - Tuo, Kaiyong (2023)
Rechargeable all-solid-state batteries (ASSBs) are considered as promising candidates for next-generation energy storage due to their high energy density and excellent safety performance. However, the low ionic conductivity of the solid-state electrolytes (SSEs) and interfacial issues are still challenging. Herein, we report a series of new mixed-metal halide superionic conductors Li3−xY1−xHfxCl6 (0 ≤ x < 1) with high ionic conductivity up to 1.49 mS cm−1 at room temperature. Using various experimental characterization techniques and bond-valence energy landscape (BVEL) calculations, we gain insights into the aliovalent substitution of Hf for Y in halide Li3YCl6 that influences the local structural environment and the underlying lithium-ion transport. Importantly, it is found that the existence of prevalent cation site disorder and defect structure as well as the synthetically optimized (Y/Hf)Cl6 framework with a more covalent feature in Hf4+-substituted Li3YCl6 strongly benefits the transport properties. In particular, the formation of an infinitely 3D connected Li+ ion diffusion pathway consisting of face-sharing octahedra within the lattice of Hf4+-substituted Li3YCl6 is revealed by structural elucidation and theoretical calculations. Additionally, owing to the exceptional interfacial stability of the as-milled SSEs against high-voltage cathode materials, all-solid-state lithium-ion batteries with a LiCoO2 cathode and Li–In anode exhibit outstanding electrochemical performance.